Current research update on group B streptococcal infection related to obstetrics and gynecology - Liu, Ying; Ai, Hao (Frontiers in Pharmacology, 2024)
Group B streptococcal (GBS) is a gram-positive bacterium that is commonly found in the gastrointestinal tract and urogenital tract. GBS infestation during pregnancy is a significant contributor to maternal and neonatal morbidity and mortality globally. This article aims to discuss the infectious diseases caused by GBS in the field of obstetrics and gynecology, as well as the challenges associated with the detection, treatment, and prevention of GBS.